1997
DOI: 10.2486/indhealth.35.367
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Effects in Workers Exposed to Benzene: With Special Reference to Exposure Biomarkers and Confounding Factors.

Abstract: The aim of the study was to establish a correlation between biomarkers of exposure and cytogenetic test results in workers occupationally exposed to benzene and toluene, with special reference to confounding factors influencing the outcome of the cytogenetic test. The incidence of structural chromosome aberrations and sister chromatid exchanges was studied in the peripheral blood lymphocytes cell genome of 49 female shoe-makers, mean age 38 years, mean length of occupational exposure 17 years and in a group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…Increased SCEs were found in the first group, but not the second (Karacic et al, 1995). Four recent reports found no increase in SCEs in benzene-exposed workers compared with controls (Bogadi-Sare et al, 1997;Carere et al, 1995;Carere et al, 1998a;Xu et al, 1998). Therefore, based on the conflicting results from these studies, the effect of benzene exposure on SCE induction remains unclear.…”
Section: Sister Chromatid Exchanges (Sces)mentioning
confidence: 44%
“…Increased SCEs were found in the first group, but not the second (Karacic et al, 1995). Four recent reports found no increase in SCEs in benzene-exposed workers compared with controls (Bogadi-Sare et al, 1997;Carere et al, 1995;Carere et al, 1998a;Xu et al, 1998). Therefore, based on the conflicting results from these studies, the effect of benzene exposure on SCE induction remains unclear.…”
Section: Sister Chromatid Exchanges (Sces)mentioning
confidence: 44%
“…Page 19 of 31 peripheral blood lymphocytes, bone marrow and sperms of people chronically exposed to benzene has become evident through different studies , Andreoli et al, 1997, Bogadi-Sare et al, 1997, Kasuba et al, 2000, Zhang et al, 2002, Morimoto, 1983. Zhang et al (2011) has reported dose-dependent chromosomal aneuploidies (monosomy & trisomy) in the peripheral blood lymphocytes of 47 workers exposed to benzene .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Nevertheless, interest in the oxidative damage caused by these solvents' toxic effects have only is relatively new, and thus the amount of evidence concerning their possible genotoxic and carcinogenic potential is scarce and still under discussion. Even though these substances are considered to be neither carcinogenic nor genotoxic to humans (IARC class 3 carcinogens, ie, not classifiable as to their carcinogenicity to humans), there is a growing amount of evidence suggesting increased (i) levels of markers of oxidative stress (10)(11)(12), (ii) rate of chromosomal aberrations or sister chromatid exchange (12)(13)(14), and (iii) incidence of various cancers among workers occupationally exposed to toluene or xylene [even at occupational exposures far below the respective occupational limits (15)(16)(17)(18)(19)(20)(21)]. Although precise mechanisms underlying the effects of toluene and xylene remain unknown, the role of oxidative stress, oxidative DNA damage and dysregulated cellular antioxidant levels have been implicated (22)(23)(24).…”
mentioning
confidence: 99%